Combination of Cas9 and adeno-associated vectors enables efficient in vivo knockdown of precise miRNAs in the rodent and primate brain - David Roura-Martinez; Natalia Popa; Florence Jaouen; Cynthia Rombaut; Catherine Lepolard; Dipankar Bachar; Ana Borges; Maxime Cazorla; Maxime Villet; Sebastien Moreno; Hélène Marie; Eduardo Gascon (Proceedings of the National Academy of Sciences, 2025)
microRNAs (miRNAs) are key regulators of multiple biological functions. Although intensively studied, inactivating miRNAs in vivo is particularly challenging, especially in the brain. Here, we designed cell-specific tools aiming at downregulating defined miRNA species in vivo and investigating their function in discrete neuronal networks. Focusing on miR-124, a miRNA highly expressed in the mammalian brain and transcribed from three independent chromosomal loci, we designed and validated different guide RNAs. In vivo, our CRISPR-Cas9 designs strongly downregulate miR-124 levels without affecting the expression of other miRNAs. As a result, levels of endogenous miR-124 targets exhibit a significant increase supporting the release of its silencing activity. We provide evidence that specific deletion of miR-124 in neural stem cells of the subventricular zone altered migration of newly generated neurons into the olfactory bulb. We also showed that our vectors modified the Ca 2+ permeability of AMPA receptors, a robust functional output downstream of miR-124. We also extended our approach to other miRNAs, mammalian species, and Cas9 proteins, confirming the versatility of CRISPR-Cas9. These tool properties support their potential for elucidating miRNA functions in complex experimental in vivo settings such as brain networks.